Philology of the flesh - Hamilton, John T. (The University of Chicago Press, 2018)
Intro -- Contents -- Author's Note -- 1. Elliptical Prolegomena -- 2. Before the Word -- 3. This Loved Philology -- 4. Implications of Citation -- 5. The Mountain and the Molehill -- 6. Carnal Inscriptions -- 7. The Stillest Night -- Acknowledgments -- Works Cited -- Index of Biblical Verses -- General Index